Severe immune thrombocytopenia following COVID-19 vaccination (Moderna) and immune checkpoint inhibitor - Chong, Kah-Meng; Yang, Ching-Yao; Lin, Chien-Chin; Lien, Wan-Ching (The American journal of emergency medicine, 2022)
Safe and effective prophylactic vaccines are urgently needed to contain the coronavirus disease 2019 (COVID-19) pandemic. However, several vaccination-related adverse effects have been reported. Here, we report a rare case of severe immune thrombocytopenia occurring 3 days after receiving the mRNA-1273 (Moderna) COVID-19 vaccine in an Asian woman with a history of refractory lung adenocarcinoma treated with durvalumab, an immune checkpoint inhibitor. Treatment with platelet transfusion (12 units) and oral prednisolone (1 mg/kg per day) significantly improved her hemoptysis with thrombocytopenia. To the best of our knowledge, this is the first case of ITP following Moderna inoculation among Asians. This study highlights a potential adverse effect of mRNA-based COVID-19 vaccines in cancer patients receiving immune checkpoint inhibitors.